Impact of gender and menopausal status on metabolic parameters in chronic hepatitis C infection. Issue 3 (10th November 2015) - Gonzales, C. A.; Bacchetti, P.; Khalili, M.
Summary: Hepatitis C infection (HCV) and menopause are associated with insulin resistance (IR), and IR accelerates HCV‐induced liver disease. The relationship between menopause and IR has not been studied in this population. This study aimed to assess the impact of menopause on IR and metabolic syndrome in HCV. One hundred and three (69 men, 16 premenopausal, 18 postmenopausal women) noncirrhotic, nondiabetic HCV‐infected adults underwent IR measurement via steady‐state plasma glucose during a 240‐min insulin suppression test. Metabolic syndrome was defined by at least three of five standard laboratory/clinical criteria. The patient characteristics were as follows: mean age 48 years, waist circumference 94.4 ± 12.4 cm and 37.9% Caucasian. SSPG was higher in postmenopausal than premenopausal women or men (mean difference 18, 95% CI −41 to 76 and 35, 95% CI −3 to 72 mg/dL; respectively). After adjusting for waist circumference, female gender, nonwhite race and triglycerides were positively associated and high‐density lipoprotein negatively associated with steady‐state plasma glucose. Compared to men, both pre‐ (Coef 48, 95% CI 12–84) and postmenopausal women (Coef 49, 95% CI 17–82) had higher steady‐state plasma glucose. Compared to premenopausal women, men (OR 2.0, 95% CI 0.38–10.2) and postmenopausal women (OR 2.9, 95% CI 0.46–18.8) had higher odds of metabolic syndrome, but this was statistically nonsignificant. Both liver inflammation (OR 7.9) and nonwhite race (OR 6.9) were associated with metabolic syndrome. We conclude that women are at inc‐reased risk for IR in HCV. There may also be an increased risk of metabolic syndrome postmenopause. Along with lifestyle modification and weight loss, women with metabolic abnormalities represent an especially at‐risk group warranting HCV treatment to prevent adverse metabolic outcomes.